1991
DOI: 10.1177/074391569101000205
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Ecologically Concerned Consumers and Their Intention to Purchase Ecologically Packaged Products

Abstract: Packaging is a major contributor to the escalating solid waste stream. This paper presents results of a study that attempts to determine variables which can be used to discriminate between groups that are and are not willing to purchase ecologically packaged products. Attitude toward ecologically conscious living, attitude toward litter, locus of control and the perception of pollution as a problem were found to be significant discriminating variables. Implications for marketers and public policymakers are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
2
13

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(250 citation statements)
references
References 30 publications
15
220
2
13
Order By: Relevance
“…In all, the conclusion to be drawn from previous research, which is expressed by some researchers (e.g. Alwitt and Pitts, 1996;Schwepker and Cornwell, 1991), is that pro-social attitudes is related but not highly correlated with behavior. Because of this, pro-social attitudes are likely to be an explanatory factor of SR investment.…”
Section: Pro-social Attitudes Regarding the Issues Addressed In Srimentioning
confidence: 80%
“…In all, the conclusion to be drawn from previous research, which is expressed by some researchers (e.g. Alwitt and Pitts, 1996;Schwepker and Cornwell, 1991), is that pro-social attitudes is related but not highly correlated with behavior. Because of this, pro-social attitudes are likely to be an explanatory factor of SR investment.…”
Section: Pro-social Attitudes Regarding the Issues Addressed In Srimentioning
confidence: 80%
“…These include demographic, religious or culture barriers (Doran 2009;Schwepker and Cornwell 1991), perceived price, quality or value of goods barriers (Loureiro and Mceachern and Schroder 2002;Roberts 1996); lack of information on the ethical credentials of products barriers (Irving et al 2002;Shaw et al 2006) and lack of availability (Dickson 2001;Hira and Ferrie 2006). However, for each of these suggestions we can find an equal number of studies suggesting they have little to no impact.…”
Section: Research Errormentioning
confidence: 87%
“…According to Bhate and Lawler (1997) and Schwepker and Cornwell (1991), there is no relationship between marital status and ethical consumer behavior. On the other hand, Auger et al (2003) and Roberts (1995) found that married consumers are more likely to behave ethically, while Dickson (2001) found ethical consumer behavior to be congruent with being unmarried.…”
Section: Achievementmentioning
confidence: 92%
“…Bhate and Lawler (1997), De Pelsmacker (2005a), Schwepker and Cornwell (1991), Shrum et al, (1995) found that gender had no influence on ethical consumer behavior. However, other studies found that women were more likely to engage in such behavior (see Blend and van Ravenswaay, 1999;Loureiro and Lotade, 2005;Mainieri et al, 1997;Roberts, 1996).…”
Section: Achievementmentioning
confidence: 95%